Science : the scientific method - Sunburst Visual Media; Cerebellum Corporation (2010)
From starting a problem to gathering data and coming to a conclusion, students demonstrate all eight steps of the scientific method.
"391120"
Grades K-8.
DVD
Keywords: Science -- Methodology